Unpacking Evaluative Meaning-Making Resources in Verbal Movie Descriptions: A Comparative Study of Native and Non-Native English Speakers - Muhammed Parviz; Alireza Jalilifar; Alexanne Don (SAGE Open)
The present study explored how native speakers (NSs) and non-native speakers (NNSs) of English exploit evaluative meaning-making resources of English when sharing their judgements and opinions on English movie descriptions. To this end, 10 native speakers of Australian English and 10 Iranian non-native speakers took part in on-line informal interviews, based on an approach known as snowball sampling. The study employed a combination of both qualitative and quantitative methods of analysis. The results revealed significant differences in the use of evaluative language between the two groups, with NNSs focusing more on Affect, Judgment and Appreciation respectively, while NSs prioritized Appreciation, followed by Affect and Judgment. The findings are discussed by reference to cultural and linguistic differences in the use of evaluative resources. Moreover, NSs relied more on invoked evaluation whereas NNSs showed a preference for inscribed evaluation. However, both groups utilized a higher frequency of positive descriptions in during their descriptions of English movies. These findings can provide valuable insights for language teaching and research, highlighting the significance of incorporating evaluative language resources into language instruction. The study further brought attention to the interconnectedness of diverse evaluative resources such as reference to emotions and judgements with complex linguistic and cultural domains.